2020
DOI: 10.1371/journal.pone.0234664
|View full text |Cite
|
Sign up to set email alerts
|

Discordant vascular parameter measurements in diabetic and non-diabetic eyes detected by different optical coherence tomography angiography devices

Abstract: To compare quantitative changes in macular parameters in diabetic patients detected by two optical coherence tomography angiography (OCTA) instruments. Methods 80 phakic eyes were classified as no diabetes, diabetes without diabetic retinopathy (DR), mild non-proliferative diabetic retinopathy (NPDR), and severe NPDR or proliferative DR (PDR). OCTA was performed using devices from two manufacturers (Zeiss and Heidelberg). Superficial and deeper vascular skeleton density (SVSD, DVSD), superficial and deeper ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…They have found that FAZ measurements were consistent across all four devices, while VAD and FD measurements showed significant variability calculated by the different devices 28 . Chen et al compared quantitative changes in macular parameters in patients with diabetes with two different OCTA machines 4 . In their research the two devices were largely inconsistent in terms of SkD and VD parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have found that FAZ measurements were consistent across all four devices, while VAD and FD measurements showed significant variability calculated by the different devices 28 . Chen et al compared quantitative changes in macular parameters in patients with diabetes with two different OCTA machines 4 . In their research the two devices were largely inconsistent in terms of SkD and VD parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In their research the two devices were largely inconsistent in terms of SkD and VD parameters. They used the size comparison index (SCI), to simplify the comparison of OCTA parameter values between the two OCTA devices 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Both the left and the right eye of each subject were examined, but only one eye of each subject was chosen to avoid bias due to the interrelation between both eyes of a participant. The right eye from each subject was included, and if the right eye image was of poor quality, the left eye was used instead [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…1 Comparison of optical coherence tomography angiography (OCTA) images from different devices. (a) : en face scans by five commercial devices at the level of superficial and deep capillary plexuses (SCP and DCP) – small circles represent the detectable microaneurysms, denoted by alphabetical letters [ 4 ]; (b) : the upper row shows en face scans at the level of SCP, DCP, and choriocapillaris (CC) obtained by two machines; the lower row shows corresponding binarized images [ 6 ] …”
Section: Main Textmentioning
confidence: 99%
“…Moreover, results from a study on 80 eyes with different DR severities showed poor agreement between Zeiss and Heidelberg OCTA devices in nearly all quantitative parameters except superficial vessel density – i.e., superficial vessel length density, deep vessel density, deep vessel length density, and choriocapillaris flow voids (Fig. 1 .b) [ 6 ]. The presence or severity of retinopathy did not affect the magnitude of discrepancy [ 6 ].…”
Section: Main Textmentioning
confidence: 99%